EFEK INTERVENSI TERSTRUKTUR TERHADAP PENURUNAN KELUHAN SINDROM PREMENSTRUASI - Hermansyah, Hermansyah; Husni, Husni; Wahyuni, Elly (Politeknik Kesehatan Kemenkes Bengkulu, 2014)
Approximately 40 % of women aged 14-50 years experiencing pre-menstrual syndrome, better known as PMS (pre-menstruation syndrome). This study aims to determine the effect of a structured intervention (counseling and natural techniques) against reducing premenstrual syndrome complaints in young women aged 12-15 years in the city of Bengkulu. This type of research is a pre-experimental, with one group pretest posttest design. The populations in this study were all girls (191 girls) in grade one of Junior High School 2, Bengkulu city in 2013. The sample was 35 samples girls taken with accidental sampling technique. Data was collected using primary data to obtain symptom of premenstrual syndrome by using a check list format and schedule student menstruation. Data analysis was performed using univariate and bivariate statistical tests by using a dependent t-test (paired t test) at α 5 % (one tail ). Results obtained by univariate analysis the average complaint premenstrual syndrome experienced by young women before intervention structured is 31.29 with a standard deviation of 7.238, the average sympton of premenstrual syndrome experienced by young women after structured interevensi is 27.86 with a standard deviation of 7.815. The results of the bivariate analysis showed a structured intervention has efffect in reducing symptom of premenstrual syndrome (p =0.022). It is suggested to do this intervention regularly in order to reduce premenstrual syndrome.